Plan de negocios para la expansión del Restaurante Alivinatu en la parroquia de Vilcabamba cantón Loja - Rengel Jara, Eduardo Vicente. (2015)
The project that has been developed seeks to expand the business scope of the restaurant Alivinatu to the village of Vilcabamba, in which the main procedure (method) is the production of organic and vegetarian food coming from its own farm, being developed in a sustainable way and promoting environmental protection. On the other hand, the development of this business plan with the gathered information neglects the empirical method, having foundation on a system that allows processes to standardize their production, service and better manage the business through the financial analysis.